Comparative education in search of a processual model for dealing with cultural diversity - Renata Nowakowska-Siuta (Studia z Teorii Wychowania)
As the world becomes more and more culturally diverse, an accurate knowledge of the influence of cultural factors on the mental processes of an individual and the construction of social capital become increasingly important for our ability to effectively understand differences in culture. How can we cope with this task in everyday life? What is the relevance of comparative education in this process? One solution could be to create a certain intellectual map of cultural similarities and differences to which we could refer at any time in order to better understand the diversity around us. Such a peculiar encyclopaedia of knowledge about the diversity of the world has not yet been created, and it is unlikely that it will, given the dynamics of social processes, the multiplicity of events and ways of understanding them. Then how can a rational model for dealing with cultural diversity be created? In this article, I want to draw attention to the importance of comparative education in the creation of such a model, taking into account the relatively new position of comparativists recognising that a considerably important role in the process of coping with cultural diversity and difference is played i.a. by dialogic memory.